Non destructive analysis of photosynthetic pigments in leaves of Sesamum indicum (L.) - Rigon, João P. G. [UNESP] (2012)
The study aimed to relate the photosynthetic pigments, which were extracted in a laboratory and the readings were obtained by the portable chlorophyll meter ClorofiLOG 1030, by using mathematical models in sesame leaves.This work was conducted in December 2010, at Embrapa Cotton, where feaf discs were removed to measure chlorophyll indexes through the portable chlorophyll meter.The same leaf discs were subjected to extraction of photosynthetic pigments, by using 5 mL dimethyl sulfoxide (DMSO), and were kept in a water bath at 70 °C for 30 min. Afterwards, an aliquot of 3 mL was removed to be read in a spectrophotometer at wavelengths of 470, 646 and 663 nm. Based on analytical results, mathematical models were adjusted by using the chlorophyll index to predict the levels of chlorophyll a, b, and total, and of carotenoids and their relationships. The study concluded that the portable chlorophyll meter ClorofiLOG 1030 can be used to estimate the concentration of photosynthetic pigments in sesame leaves with high precision, besides saving resources and time.